Creating Tomorrows Schools Today. Education Our Children Their Futures - Fernández Fernández, Raquel (Pulso. Revista de educación, 2013)
Review of the book:Gerver, R. (2010). Creating Tomorrows Schools Today. Education Our Children Their Futures. Continuum Books.